2013
DOI: 10.1007/s00284-013-0379-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Calcite Nanocrystal by a Urease-Positive Strain of Enterobacter ludwigii and Study of Its Structure by SEM

Abstract: The present research aimed at evaluating the effects of urease enzyme and increasing pH on calcite nanocrystal formation. Unlike some researches, the results showed that CaCO3 precipitation is not a general phenomenon among the bacteria and if a bacterium has not this ability, it will not be able to produce calcite even with an increase in pH. All urease-positive bacteria had this ability, while only some urease-negative bacteria were able to produce calcite. Production and characterization of nanocrystals on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Ureolytic microorganisms have been shown to be promising candidates for the formation of metal carbonates (Ferris et al 2004 ; Ghashghaei and Emtiazi 2013 ; Phillips et al 2013 ; Li et al 2014 , 2015 , 2016 ; Kumari et al 2016 ). Previous research has demonstrated that N. crassa was particularly effective for precipitation of CaCO 3 and over 90% of supplied calcium (50 mM) was precipitated as calcite (CaCO 3 ) (Li et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ureolytic microorganisms have been shown to be promising candidates for the formation of metal carbonates (Ferris et al 2004 ; Ghashghaei and Emtiazi 2013 ; Phillips et al 2013 ; Li et al 2014 , 2015 , 2016 ; Kumari et al 2016 ). Previous research has demonstrated that N. crassa was particularly effective for precipitation of CaCO 3 and over 90% of supplied calcium (50 mM) was precipitated as calcite (CaCO 3 ) (Li et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Definitive proofs of involvement of bacterial cell surfaces in complex environments on the nucleation process are rare. Ghashghaei and Emtiazi [33] reported the presence of nanocrystals of CaCO 3 on cell walls of the bacteria Enterobacter ludwigii for experiments performed with a liquid culture. While the data is suggestive of the role of cell wall, a more definite proof is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and size of CaCO3 crystals depend on the molecular properties of exopolysaccharides secreted by bacterial cells, as well as on the colony form [14]. Furthermore, spherical CaCO3 crystals, vaterites, are primarily formed in solid medium containing agar [15]. Figure 2B shows typical time courses for pH, cell growth, and CaCO 3 formation in the urea-CaCl 2 broth.…”
Section: Caco3 Formation In Solid and Liquid Mediamentioning
confidence: 99%